European navies and the conduct of war - James, Alan 1965-; Alfaro Zaforteza, Carlos; Murfett, Malcolm H. (Routledge, 2019)
"European Navies and the Conduct of War considers the different contexts within which European Navies have operated over a period of 500 years culminating in World War Two, the greatest war ever fought at sea. Chronological in structure, the book is the ideal resource for students and scholars of naval and military history"--